Новый род и новый вид клещей семейства Acaridae (Acariformes, Acaroidea) из морских водорослей - Волгин, В.И.; Щур, Л.Е. (Вестник зоологии, 1974)
A description is given of a new genus Phycogitum and species Ph. ponticus of mites of the Acaridae family, small colony of which was found in sea algae cast ashore in the territory of the Potievkian part of the Black Sea reservation (the Kherson region of the Ukrainian SSR).